The Top 20 (Plus 5) Technologies for the World Ahead. - Irvine, James H.; Schwarzbach, Sandra (Futurist)
Around ten years ago, military analysts at the Naval Air Warfare Center in Southern California set out to determine how emerging technologies could transform armed conflict over the next 25 to 50 years. They chose 200 new technological applications, projecting out their growth and how they might affect future military strategy and warfare. They concluded that these technologies would be major drivers of not just future military affairs, but of almost all of human life. From these 200, the writers, military analysts at the Naval Air Warfare Center, examine what they consider the top 20 innovations that will have the greatest effect in the short term, as well as picking five other feasible technological developments that could significantly change the world in the more distant future.